BABY, Sophie; COMPAGNON, Olivier y GONZÁLEZ CALLEJA, Eduardo: Violencia y transiciones políticas a finales del siglo XX. Europa del Sur-América Latina. Madrid: Casa de Velázquez, 2009, 311 pp - De La Fuente Ruiz, Juan José (Studia Historica. Historia Contemporánea, 2011)
Reseña